Synthesis and characterization of amphiphilic polyurethanes as coating materials for urinary catheters - Park, Jae Hyung; Kim, Kwangmeyung; Chung, Hesson; Kwon, Ick Chan; Bae, You Han; Jeong, Seo Young (POLYMER SOC KOREA, 2006)
The long-term use of indwelling urinary catheters can allow bacterial adhesion to their surfaces, followed by the catheter-associated urinary tract infection. In an attempt to minimize the bacterial adhesion, various amphiphilic polyurethanes (APUs) were synthesized as potential coating materials for urinary catheters. By varying composition of the soft segments such as PEO. PTMO. and PDMS, four different polyurethanes were synthesized. All the APU-coated urinary catheters had the smooth surfaces and showed higher hydrophilicity, compared to the commercial silicone catheters. In particular, the use of APUs with the higher PEG content significantly augmented hydrophilicity and remarkably reduced the total amount of bacteria adhering to the surface. Overall. the APUs prepared in this study provided the promising potential as coating materials for urinary catheters.
Keywords: PDMS-BASED POLYURETHANES; POLY(TETRAMETHYLENE OXIDE); POLY(DIMETHYL SILOXANE); POLY(ETHYLENE OXIDE); TRACT INFECTIONS; BACTERIAL ADHESION; URETHRAL CATHETERS; PLATELET-ADHESION; MPEG GRAFTS; ENCRUSTATION